"Here we are part of a living culture": Understanding the cultural determinants of health in Aboriginal gathering places in Victoria, Australia. (November 2018) - Kingsley, Jonathan; Munro-Harrison, Emily; Jenkins, Anne; Thorpe, Alister
Abstract: This article provides an exploration of the cultural determinants of health, based on a research evaluation investigating a number of Aboriginal gathering places in Victoria (Australia). Gathering places are recognised as settings in which people practice and learn about local Aboriginal culture, history and place. Academic literature on gathering places is sparse. Thirteen gathering places were evaluated in this research. Each site is unique and has a specific story that connects it to the history and geography of the place in which it is located. Sixty-nine gathering place members participated in qualitative semi-structured interviews or focus groups. Using thematic analysis, the findings were divided into four key themes associated with cultural determinants of health (social networks; inclusiveness; empowerment; connections). These elements create a safe place to learn about culture and Country, and support an environment for strengthening identity, improving health and building resilience. The findings from this study highlight the benefits of using gathering places to explore the cultural determinants of health. Highlights: Cultural determinants of health enhance individual and community identity, wellbeing and resilience. Aboriginal Victorian gathering places provide safe spaces to practice and learn Aboriginal culture. Gathering places encourage healing and wellbeing creating inclusive and empowering spaces. Gathering places provide a sense of place, especially for people who have been marginalised. Gathering places could be replicated to create safe and culturally competent services in other communities.